Transforming Uganda’s Public Policy, Economy, and Politics; What we must do to make Uganda better - Tabaire, Bernard; Okao, Jackie (ACODE, 2010)
"Who should improve things? That is a question posed at the 7th meeting of the State of the Nation Platform, most of whose members fall in the dissatisfied age group. Appropriately, the discussion was led by a panel drawn from amongst the STON members to compel self-reflection. After all, those who are younger and economically active largely drive transformation of society. What is the vision, mission and objective of our generation? Why are we living at this time? What do we want to change? What future do we need? What means are we going to use to achieve that future? Who is going to lead us? Are we just making comments and leaving it at that? What are our own value systems as a generation, as Ugandans? Are we not making an assumption that we are talking about a homogenous generation? The questions did not have to be answered fully and immediately but, if anything, they sparked off some good amount of serious thinking about the state of affairs in Uganda."
Keywords: Public Policy, Economy, and Politics; Transforming